Reflective film
By placing the base film, the metal reflective layer, the metal compound layer and the cured resin layer in the reflective film, the corrosion problem of metal reflective layer is solved, and the high corrosion resistance and optical performance of the reflective film are improved.
Patent Information
- Application Number
- CN202410926944.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-14
- Filing Date
- 2024-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The metal reflective layer of the conventional reflective film is susceptible to water vapor corrosion, resulting in deterioration of optical properties and making it difficult to effectively suppress corrosion.
The base film, metal reflective layer, metal compound layer and cured resin layer are arranged in sequence in the thickness direction of the reflective film. The metal compound layer is used to block water vapor and prevent it from penetrate into the metal reflective layer. The cured resin layer provides hardness and scratch resistance. sex.
The corrosion of the metal reflective layer is effectively suppressed, the corrosion resistance and optical properties of the reflective film are improved, and the effective reflection of light and light leakage is ensured.
Smart Images

Figure CN119310663A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to reflective films. Background Art
[0002] A liquid crystal display device comprises: a liquid crystal panel having an image display surface, a backlight source (backlight) emitting light toward the back side of the panel, and a housing for accommodating them. The housing has a frame (bezel) portion as a frame surrounding the image display surface. A reflective film is arranged on the inner wall surface in the frame portion. The reflective film reflects the light from the backlight source toward the liquid crystal panel in the frame portion. Thus, the light from the backlight source is effectively utilized. Such a reflective film is described, for example, in the following patent document 1.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2000-187207
[0006] Patent Document 1 describes a reflective film including, in order in the thickness direction, a base film, a metal reflective layer, and a protective resin layer. Light is reflected by the metal reflective layer.
[0007] On the other hand, it is strongly required that the metal reflection layer of the reflection film is less likely to be corroded. The reason for this is to suppress the degradation of optical characteristics such as reflection characteristics in the reflection film due to metal corrosion. Summary of the invention
[0008] The present invention provides a reflective film suitable for suppressing corrosion of a metal reflective layer.
[0009] The present invention [1] includes a reflective film comprising, in order in the thickness direction: a base film, a metal reflective layer, a metal compound layer, and a cured resin layer.
[0010] The present invention [2] includes the reflective film described in the above [1], wherein the metal reflective layer is an aluminum layer.
[0011] The present invention [3] includes the reflective film described in [1] or [2] above, wherein the metal compound layer is an indium oxide layer, an aluminum nitride layer or a copper indium oxide layer.
[0012] The present invention [4] includes the reflective film according to any one of [1] to [3] above, wherein the thickness of the metal compound layer is 5 nm or more.
[0013] Effects of the Invention
[0014] As described above, the reflective film of the present invention comprises, in order in the thickness direction: a substrate film, a metal reflective layer, a metal compound layer, and a cured resin layer. The reflective film having the metal compound layer on the metal reflective layer is suitable for inhibiting water vapor from penetrating into the metal reflective layer from the side opposite to the substrate film. By inhibiting the penetration of water vapor, corrosion caused by water vapor is inhibited in the metal reflective layer. Therefore, the reflective film of the present invention is suitable for inhibiting corrosion of the metal reflective layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic cross-sectional view of one embodiment of the reflective film of the present invention.
[0016] Figure 2A to Figure 2D express Figure 1 The manufacturing method of the reflective film shown. Figure 2A It shows the process of preparing the base film. Figure 2B It represents the process of forming a metal reflective layer on a substrate film. Figure 2C represents a process of forming a metal oxide layer on the metal reflective layer, Figure 2D This shows the step of forming a cured resin layer on the metal oxide layer.
[0017] Description of Reference Numerals
[0018] X: reflective film; H: thickness direction; 10: substrate film; 11: first surface; 12: second surface; 20: metal reflective layer; 30: metal compound layer; 40: cured resin layer. DETAILED DESCRIPTION
[0019] A reflective film X according to one embodiment of the present invention is as follows Figure 1 As shown, the substrate film 10, the metal reflective layer 20, the metal compound layer 30 and the cured resin layer 40 are provided in order in the thickness direction H. The reflective film X extends in a direction (surface direction) orthogonal to the thickness direction H. The reflective film X is, for example, a reflective film for preventing light from a backlight source of a liquid crystal display device from leaking from a housing.
[0020] The substrate film 10 is a substrate for ensuring the strength of the reflective film X. The substrate film 10 has a first surface 11 and a second surface 12 on the opposite side of the first surface 11. In addition, the substrate film 10 is, for example, a transparent resin film having flexibility. As the material of the substrate film 10, for example, polyester resin, polyolefin resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin and polystyrene resin can be listed. As polyester resin, for example, polyethylene terephthalate (PET), polybutylene terephthalate and polyethylene naphthalate can be listed. As polyolefin resin, for example, polyethylene, polypropylene and cycloolefin polymer can be listed. As acrylic resin, for example, polymethacrylate can be listed. From the viewpoint of transparency and strength, the material of the substrate film 10 is preferably polyester resin, more preferably PET.
[0021] From the viewpoint of ensuring the meaningful light reflectivity of the substrate film 10, the substrate film 10 is preferably a white film. The white film is obtained, for example, by containing particles such as inorganic fillers that scatter light in the resin film. As materials for such particles, for example, titanium oxide, calcium carbonate, barium sulfate, silicon dioxide and talc can be listed, and at least one selected from the group consisting of titanium oxide and silicon dioxide is preferably used. These particles can be used alone or in combination of two or more. The average particle size of the particles is, for example, greater than 0.05 μm, preferably greater than 0.1 μm, and, for example, less than 2 μm, preferably less than 1 μm. The content ratio of the particles in the substrate film 10 as a white film is, for example, greater than 5% by mass, preferably greater than 10% by mass, and, for example, less than 50% by mass, preferably less than 40% by mass.
[0022] The thickness of the base film 10 is preferably 20 μm or more, more preferably 30 μm or more, and further preferably 35 μm or more from the viewpoint of suppressing the penetration of water vapor from the base film 10 side of the reflective film X to the metal reflective layer 20 and from the viewpoint of the strength of the reflective film X. From the viewpoint of ensuring the operability of the base film 10 in the roll-to-roll method, the thickness of the base film 10 is preferably 300 μm or less, more preferably 200 μm or less, and further preferably 150 μm or less.
[0023] The first surface 11 of the substrate film 10 may be subjected to a surface modification treatment to ensure adhesion of the metal reflective layer 20 to the substrate film 10. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.
[0024] In the present embodiment, the metal reflective layer 20 is disposed on the first surface 11 of the base film 10. That is, the metal reflective layer 20 is in contact with the first surface 11 in the present embodiment.
[0025] The metal reflective layer 20 is formed of a metal (first metal) having light reflectivity. Examples of the first metal include aluminum (Al), silver (Ag), titanium (Ti), and alloys thereof. From the perspective of ensuring good light reflectivity of the metal reflective layer 20 to visible light, aluminum or silver is preferably used as the first metal. That is, the metal reflective layer 20 is an aluminum layer or a silver layer.
[0026] From the viewpoint of ensuring the light reflectivity of the metal reflective layer 20 and the reflective film X, the thickness of the metal reflective layer 20 is preferably 30 nm or more, more preferably 50 nm or more, and further preferably 70 nm or more. From the viewpoint of ensuring the adhesion of the metal reflective layer 20 to the base film 10, the thickness of the metal reflective layer 20 is preferably 500 nm or less, more preferably 300 nm or less, further preferably 200 nm or less, further preferably 150 nm or less, and further preferably 120 nm or less.
[0027] The metal compound layer 30 is arranged on the metal reflective layer 20 in the present embodiment. That is, the metal compound layer 30 is in contact with the metal reflective layer 20 in the present embodiment. The metal compound forming the metal compound layer 30 is a compound of a metal and a non-metal. The metal compound layer 30 is a layer formed only of a metal compound. As the metal compound, for example, metal oxides, metal nitrides, and metal carbides can be listed. As the metal (second metal) in the metal compound, for example, indium (In), copper (Cu), aluminum (Al), zinc (Zn), tin (Sn), magnesium (Mg), nickel (Ni), cobalt (Co), and chromium (Cr) can be listed. From the viewpoint of ensuring the water vapor barrier property of the metal compound layer 30, the second metal is at least one selected from the group consisting of In, Cu, Al, Zn, Sn, Mg, Ni, Co, and Cr. From the viewpoint of ensuring the water vapor barrier property of the metal compound layer 30, the metal compound is preferably an oxide or nitride of the second metal, and more preferably indium oxide, aluminum nitride, or copper indium oxide. That is, the metal compound layer 30 is preferably an indium oxide layer, an aluminum nitride layer or a copper indium oxide layer. The copper indium oxide may also contain copper oxide and indium oxide. The copper oxide is copper (I) oxide and / or copper (II) oxide.
[0028] From the viewpoint of ensuring the water vapor barrier property of the metal compound layer 30, the thickness of the metal compound layer 30 is preferably 5 nm or more, more preferably 10 nm or more, and further preferably 15 nm or more. From the viewpoint of ensuring the adhesion of the metal compound layer 30 to the metal reflective layer 20, the thickness of the metal compound layer 30 is preferably 200 nm or less, more preferably 150 nm or less, and further preferably 100 nm or less.
[0029] In the present embodiment, the cured resin layer 40 is disposed on the metal compound layer 30. That is, in the present embodiment, the cured resin layer 40 is in contact with the metal compound layer 30. The cured resin layer 40 is a hard coating layer for preventing the reflective film X from being scratched.
[0030] The cured resin layer 40 is a cured product of a curable resin composition. The curable resin composition contains a curable resin. Examples of curable resins include polyester resins, acrylic urethane resins, acrylic resins (excluding acrylic urethane resins), urethane resins (excluding acrylic urethane resins), amide resins, silicone resins, epoxy resins, and melamine resins. These curable resins may be used alone or in combination of two or more. From the perspective of ensuring the high hardness of the cured resin layer 40, it is preferred that at least one selected from the group consisting of acrylic urethane resins and acrylic resins be used as the curable resin.
[0031] Examples of the curable resin include ultraviolet curable resins and thermosetting resins. The ultraviolet curable resin is preferably an ultraviolet curable resin because it can be cured without high-temperature heating and thus contributes to improving the production efficiency of the reflective film X.
[0032] The curable resin composition may also contain particles. As particles, for example, inorganic oxide particles and organic particles can be listed. As materials for inorganic oxide particles, for example, silica, alumina, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide and antimony oxide can be listed. As materials for organic particles, for example, polymethyl methacrylate, polystyrene, polyurethane, acrylic acid-styrene copolymer, benzoguanamine, melamine and polycarbonate can be listed. The particles can be used alone or in combination of two or more. As particles, inorganic oxide particles are preferably used, and at least one selected from silica particles and zirconium oxide particles is more preferably used.
[0033] From the viewpoint of ensuring the hardness of the cured resin layer 40, the average particle size (D50) of the particles is preferably 20 nm or more, more preferably 25 nm or more, and further preferably 30 nm or more. From the viewpoint of uniform dispersion of the particles in the cured resin layer 40, the average particle size (D50) of the particles is preferably 300 nm or less, and particularly preferably 100 nm or less. The average particle size (D50) of the particles is the median particle size in the volume-based particle size distribution (the particle size at which the volume cumulative frequency reaches 50% from the small diameter side), for example, based on the particle size distribution obtained by the laser diffraction / scattering method.
[0034] From the viewpoint of ensuring the hardness of the cured resin layer 40, the proportion of particles in the cured resin layer 40 is preferably 5% by mass or more, more preferably 8% by mass or more, and further preferably 10% by mass or more. From the viewpoint of uniform dispersion of particles in the cured resin layer 40, the proportion of particles in the cured resin layer 40 is preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less.
[0035] From the viewpoint of achieving sufficient scratch resistance in the cured resin layer 40, the thickness of the cured resin layer 40 is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 0.7 μm or more. From the viewpoint of ensuring the adhesion of the cured resin layer 40 to the metal compound layer 30, the thickness of the cured resin layer 40 is preferably 5 μm or less, more preferably 3 μm or less, further preferably 2 μm or less, and further preferably 1.5 μm or less.
[0036] From the viewpoint of ensuring the light leakage prevention property of the reflective film X described later, the visual reflectance (Y value) of the reflective film X at a wavelength of 380 nm to 780 nm in the CIE-XYZ color system is preferably 80% or more, more preferably 82% or more, and further preferably 85% or more. The visual reflectance is, for example, 90% or less, 95% or less, or 100% or less. The visual reflectance (Y value) of the reflective film X refers to the reflectance of light irradiated to the reflective film X from the substrate film 10 side.
[0037] From the viewpoint of ensuring the light leakage prevention property of the reflective film X described later, the visual transmittance (Y value) of the reflective film X at a wavelength of 380 nm to 780 nm in the CIE-XYZ color system is preferably 0.10% or less, more preferably 0.09% or less, and further preferably 0.07% or less. The visual transmittance is, for example, 0.001% or more, 0.005% or more, or 0.01% or more. The visual transmittance (Y value) of the reflective film X refers to the transmittance of light irradiated to the reflective film X from the substrate film 10 side.
[0038] The reflective film X is produced in the roll-to-roll method, for example, as follows.
[0039] First, if Figure 2A As shown, a substrate film 10 is prepared (substrate film preparation step). The first surface 11 of the substrate film 10 is subjected to surface modification treatment as required. When plasma treatment is performed as the surface modification treatment, argon gas is used as an inert gas, for example. In addition, the discharge power in the plasma treatment is, for example, 10 W or more, and, for example, 5000 W or less.
[0040] Then, if Figure 2BAs shown, a metal reflective layer 20 is formed on the base film 10 (metal reflective layer forming step). Specifically, a metal film is formed on the first surface 11 of the base film 10 by a dry coating method to form the metal reflective layer 20. Examples of the dry coating method include sputtering and vapor deposition, and sputtering is preferred.
[0041] In the sputtering method, for example, a sputtering film forming device that can perform a film forming process in a roll-to-roll manner is used. In the sputtering method, specifically, a sputtering gas (inert gas) is introduced into a film forming chamber of the sputtering film forming device under vacuum conditions, and a negative voltage is applied to a target disposed on a cathode in the film forming chamber. As a result, a glow discharge is generated, gas atoms are ionized, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and the ejected target material is deposited on the substrate film 10.
[0042] The material of the target disposed on the cathode in the sputtering method (i.e., the material of the metal reflective layer 20) is, for example, the metal described above with respect to the metal reflective layer 20. The gas pressure in the film forming chamber in the film forming by the sputtering method (sputtering film forming) is, for example, 0.02 Pa or more, and, for example, 1 Pa or less. As a power source for applying a voltage to the target, for example, a DC power supply, an AC power supply, an MF power supply, and an RF power supply can be listed (the same also in the sputtering film forming described later with respect to the metal compound layer 30). The absolute value of the discharge voltage in the sputtering film forming is, for example, 50 V or more, and, for example, 500 V or less (the same also in the sputtering film forming described later with respect to the metal compound layer 30).
[0043] Then, if Figure 2C As shown, a metal compound layer 30 is formed on the metal reflective layer 20 (metal compound layer forming step). Specifically, a material is formed into a film on the metal reflective layer 20 by a dry coating method to form the metal compound layer 30. Examples of the dry coating method include sputtering and vapor deposition, and sputtering is preferred.
[0044] The material of the target configured on the cathode in the sputtering method is, for example, a sintered body of the metal compound described above with respect to the metal compound layer 30. The sputtering method can also be a reactive sputtering method. In the reactive sputtering method, in addition to the sputtering gas, a reactive gas is also introduced into the film forming chamber. In the case of forming a metal oxide film in this process, oxygen (O2) is used as the reactive gas. In the case of forming a metal nitride film in this process, nitrogen (N2) is used as the reactive gas. The material of the target configured on the cathode in the reactive sputtering method is, for example, the metal (second metal) described above with respect to the metal compound layer 30. In addition, the target material configured on the cathode in the reactive sputtering method can also use the above-mentioned metal compound and the above-mentioned metal (second metal) in combination. In the reactive sputtering method, the amount of the reactive gas introduced into the film forming chamber is, for example, more than 1 part by volume per 100 parts by volume of the amount of the sputtering gas introduced, and, for example, less than 20 parts by volume. In addition, the gas pressure in the film formation chamber during the sputtering film formation of the metallic compound layer 30 is, for example, 0.02 Pa or more, and, for example, 1 Pa or less.
[0045] The series of processes from the metal reflective layer forming step to the metal compound layer forming step are implemented using a single pass line while conveying the working film in a roll-to-roll manner. In the process using the single pass line, the working film is not released into the atmosphere once. Forming the metal compound layer 30 on the metal reflective layer 20 without releasing the working film into the atmosphere after the metal reflective layer 20 is formed helps to ensure the adhesion of the metal compound layer 30 to the metal reflective layer 20.
[0046] Then, if Figure 2D As shown, a cured resin layer 40 is formed on the metal compound layer 30 (cured resin layer forming step). The cured resin layer 40 can be formed by coating the above-mentioned curable resin composition on the metal compound layer 30, forming a coating film, and then curing the coating film. When the curable resin composition contains an ultraviolet curable resin, the coating film is cured by ultraviolet irradiation. When the curable resin composition contains a thermosetting resin, the coating film is cured by heating.
[0047] As described above, the reflective film X can be manufactured.
[0048] As described above, the reflective film X includes: the base film 10, the metal reflective layer 20, the metal compound layer 30, and the cured resin layer 40 in order in the thickness direction H. The reflective film X includes the metal compound layer 30 on the metal reflective layer 20, which is suitable for suppressing the penetration of water vapor into the metal reflective layer 20 from the side opposite to the base film 10. By suppressing the penetration of water vapor, corrosion caused by water vapor is suppressed in the metal reflective layer 20. Therefore, the reflective film X is suitable for suppressing the corrosion of the metal reflective layer 20. Specifically, as shown in the embodiments described later.
[0049] Example
[0050] The present invention is specifically described below with reference to the following examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the following amounts (contents), physical property values, parameters, etc. can be replaced by the upper limits (values defined as "below" or "less than") or lower limits (values defined as "above" or "greater than") of the amounts (contents), physical property values, parameters, etc. corresponding to them recorded in the above-mentioned "Specific Embodiments".
[0051] [Example 1]
[0052] First, a white polyethylene terephthalate (PET) film (product name "Lumirror E20", thickness 38 μm, manufactured by Toray) was prepared as a base film.
[0053] Next, a metal reflective layer and a metal oxide layer are sequentially formed on one surface (first surface) of the PET film by sputtering (sputtering film forming process). In the sputtering film forming process, a roll-to-roll sputtering film forming device (DC magnetron sputtering film forming device) is used. The device comprises: a withdrawal chamber, a first film forming chamber, a second film forming chamber, and a winding chamber. The withdrawal chamber is provided with a withdrawal roller. A roll of the above-mentioned base film as a working film is mounted on the withdrawal roller. The winding chamber is provided with a winding roller capable of winding up the working film. In the first and second film forming chambers, the working film can be moved from the withdrawal chamber to the winding chamber by a roll-to-roll method, and the film forming process is implemented.
[0054] In the sputtering film forming process, specifically, the first sputtering film forming in the first film forming chamber and the second sputtering film forming in the second film forming chamber are sequentially performed, and then the working film (substrate film / metal reflective layer / metal oxide layer) is wound up on the winding roller of the winding chamber. In the first sputtering film forming, a metal reflective layer (Al) with a thickness of 75nm is formed on the first surface of the PET film. Then, in the second sputtering film forming, a metal oxide layer (ITO) with a thickness of 50nm is formed on the metal reflective layer. The specific details of each sputtering film forming are as follows.
[0055] In the first sputtering film formation, after the sputtering film formation device (extraction chamber, first and second film formation chambers, winding chamber) is vacuum evacuated, argon (Ar) is introduced into the first film formation chamber as a sputtering gas, and the gas pressure in the first film formation chamber is set to 0.3-0.4 Pa. As a target, an Al target (manufactured by Mitsui Mining Co., Ltd.) is used. As a power source for applying voltage to the target, a DC power source is used. The film formation temperature (the temperature of the substrate film for stacking the Al layer) is set to 40°C. The type of power source and the film formation temperature are the same in the second sputtering film formation.
[0056] In the second sputtering film formation, after the above-mentioned vacuum exhaust of the sputtering film forming device, Ar as a sputtering gas is introduced into the second film forming chamber, and the gas pressure in the second film forming chamber is set to 0.3 to 0.4 Pa. In addition, as a target, an ITO target (a composite oxide of indium oxide and tin oxide, tin oxide concentration of 10% by mass, manufactured by Mitsui Mining & Co., Ltd.) is used.
[0057] Next, a curable resin composition was applied on the metal oxide layer to form a coating. The curable resin composition contained an ultraviolet curable acrylic urethane resin (product name "AICAAITRON Z844", manufactured by AICA Industries) and methyl ethyl ketone as a solvent. Next, the coating was dried and then cured by ultraviolet irradiation to form a hard coating (HC) layer with a thickness of 1 μm.
[0058] As described above, a reflective film of Example 1 was produced. The reflective film of Example 1 has a laminated structure of a substrate film (PET, thickness 38 μm), a metal reflective layer (Al, thickness 75 nm), a metal oxide layer (ITO, thickness 50 nm) and a HC layer (thickness 1 μm). In Example 1, the metal reflective layer, the metal oxide layer and the HC layer on the substrate film form a multilayer film.
[0059] [Example 2]
[0060] The reflective film of Example 2 was produced in the same manner as the reflective film of Example 1 except for the following contents. In the second sputtering film formation of the sputtering film formation process, a metal nitride layer (AlNx, thickness 50 nm) was formed instead of the metal oxide layer. In the second sputtering film formation, after the vacuum exhaust of the sputtering film forming device, Ar as a sputtering gas and nitrogen (N2) as a reactive gas were introduced into the second film forming chamber, and the gas pressure in the second film forming chamber was set to 0.3 to 0.4 Pa (reactive sputtering). The amount of N2 introduced into the second film forming chamber was set to 1 part by volume for every 15 parts by volume of Ar introduced (the flow ratio of Ar to N2 was 15:1). In addition, an Al target (manufactured by Mitsui Mining & Co., Ltd.) was used as a target. In Example 2, the metal reflective layer, the metal nitride layer, and the HC layer on the substrate film formed a multilayer film.
[0061] [Example 3]
[0062] The reflective film of Example 3 was produced in the same manner as the reflective film of Example 1 except for the following contents. In the second sputtering film formation of the sputtering film formation process, a metal nitride layer (AlNx, thickness 15 nm) was formed instead of the metal oxide layer. In the second sputtering film formation, after the vacuum exhaust of the sputtering film forming device, Ar as a sputtering gas and nitrogen (N2) as a reactive gas were introduced into the second film forming chamber, and the gas pressure in the second film forming chamber was set to 0.3 to 0.4 Pa (reactive sputtering). The amount of N2 introduced into the second film forming chamber was set to 1 part by volume for every 15 parts by volume of Ar introduced (the flow ratio of Ar to N2 was 15:1). In addition, an Al target (manufactured by Mitsui Mining & Co., Ltd.) was used as a target. In Example 3, the metal reflective layer, the metal nitride layer, and the HC layer on the substrate film formed a multilayer film.
[0063] [Example 4]
[0064] The reflective film of Example 4 was produced in the same manner as the reflective film of Example 1 except for the following contents. In the second sputtering film formation of the sputtering film formation process, a copper indium oxide layer (In2O3+copper oxide (CuO, Cu2O), thickness 50nm) was formed instead of the ITO layer as a metal oxide layer. In the second sputtering film formation, after the vacuum exhaust of the sputtering film forming device, Ar as a sputtering gas and oxygen (O2) as a reactive gas were introduced into the second film forming chamber, and the gas pressure in the second film forming chamber was set to 0.3 to 0.4Pa (reactive sputtering). The amount of O2 introduced into the second film forming chamber was set to 1 volume part for every 20 volume parts of Ar introduced (the flow ratio of Ar to O2 was 20:1). In addition, a sintered body of indium oxide (In2O3) and copper (Cu) (product name "DIABLA12", In ratio 67.3 (±3) mass %, manufactured by Mitsubishi Materials Co., Ltd.) was used. In Example 4, the metal reflective layer, the metal oxide layer, and the HC layer on the base film form a multilayer film.
[0065] [Comparative Example 1]
[0066] The reflective film of Comparative Example 1 was produced in the same manner as the reflective film of Example 1 except for the following. In the sputtering film forming process, the second sputtering film forming was not performed. That is, the metal compound layer was not formed on the metal reflective layer. In Comparative Example 1, the metal reflective layer and the HC layer on the substrate film formed a multilayer film.
[0067] [Comparative Example 2]
[0068] The reflective film of Comparative Example 2 was prepared in the same manner as the reflective film of Example 1 except for the following contents. In the second sputtering film formation of the sputtering film formation process, a mixed layer (In2O3+Cu, thickness 50nm) was formed instead of the metal oxide layer. In the second sputtering film formation, after the above-mentioned vacuum exhaust of the sputtering film forming device, Ar was introduced into the second film forming chamber as a sputtering gas, and the gas pressure in the second film forming chamber was set to 0.3-0.4Pa. In addition, as a target, a sintered body of indium oxide (In2O3) and copper (Cu) (product name "DIABLA12", In ratio 67.3 (±3) mass%, manufactured by Mitsubishi Materials) was used.
[0069] 〈Thickness of each layer〉
[0070] The thickness of each layer in the reflective film of Examples 1 to 4 and Comparative Examples 1 and 2 was measured by observation using a field emission transmission electron microscope (FE-TEM). Specifically, first, samples for cross-sectional observation of each multilayer film of Examples 1 to 4 and Comparative Examples 1 and 2 were prepared by the FIB microsampling method. In the FIB microsampling method, a FIB device (product name "FB2200", manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the cross section of the multilayer film in the cross-sectional observation sample was observed using FE-TEM, and the thickness of the metal reflective layer, the metal oxide layer (Examples 1 and 4), the metal nitride layer (Examples 2 and 3), and the mixed layer (Comparative Example 2) was measured in the observed image. In this observation, a FE-TEM device (product name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV. The measurement results are shown in Table 1.
[0071] 〈Visual transmittance〉
[0072] The visual transmittance of each reflective film of Examples 1 to 4 and Comparative Examples 1 and 2 was measured. The specific details are as follows.
[0073] First, a film sheet (first film sheet) for measurement is cut out from the reflective film. Next, the visual transmittance of the first film sheet is measured using a spectrophotometer (product name "U-4100", manufactured by Hitachi High-Tech Science). The transmittance is the visual transmittance (Y value) of the transmitted light of the wavelength of 380nm to 780nm of the first film sheet in the CIE-XYZ color system. In this measurement, the first film sheet is set in the spectrophotometer in such a way that light is irradiated from the substrate film side of the first film sheet to the first film sheet. The measurement results are shown in Table 1.
[0074] 〈Visual reflectivity〉
[0075] The visual reflectance of each reflective film of Examples 1 to 4 and Comparative Examples 1 and 2 was measured. The details are as follows.
[0076] First, the side of the reflective film opposite to the substrate film side is bonded to a black acrylic plate with the aid of a specified adhesive. Thus, a laminated film is obtained. Next, a film piece (second film piece) for measurement is cut out from the laminated film. Next, the visual reflectance of the second film piece is measured using a spectrophotometer (product name "U-4100", manufactured by Hitachi High-Tech Science Co., Ltd.). The reflectance is the visual reflectance (Y value) in the CIE-XYZ colorimetric system for irradiated light of a wavelength of 380nm to 780nm for the second film piece. In this measurement, the second film piece is placed in the spectrophotometer in such a way that light is irradiated from the substrate film side of the second film piece to the second film piece. The measurement results are shown in Table 1.
[0077] 〈Peel test〉
[0078] For each of the reflective films of Examples 1 to 4 and Comparative Examples 1 and 2, the adhesion of the multilayer film was investigated as follows.
[0079] First, a sample film was prepared for each reflective film. In the preparation of the sample film, first, a film sheet (50 mm × 50 mm) was cut from the reflective film. Next, the multilayer film on the substrate film in the film sheet was formed with 11 parallel first cuts (1 mm intervals) extending linearly in a first direction and 11 parallel second cuts (1 mm intervals) extending linearly in a second direction orthogonal to the first direction, and 100 squares were formed by the first cuts and the second cuts. Thus, a sample film was obtained. Each cut reached from the exposed surface of the multilayer film to the substrate film in the thickness direction.
[0080] Next, a peeling test (checkerboard peeling test) was performed on each sample film in accordance with JIS K 5400. Specifically, first, a prescribed single-sided adhesive tape was pasted on the multilayer film surface of the sample film in a manner covering all 100 squares. Next, the adhesive tape was peeled off along the first direction. Then, the squares after peeling off the adhesive tape were observed to confirm whether the squares were peeled off. In each of the reflective films of Examples 1 to 4 and Comparative Examples 1 and 2, the number of squares that were at least partially peeled off was 0 (no peeling occurred in any square).
[0081] 〈Corrosion test〉
[0082] The first corrosion test was performed on each of the reflective films of Examples 1 to 4 and Comparative Examples 1 and 2 as described below.
[0083] First, a sample film (210 mm × 297 mm) was cut out from the reflective film. Next, the multilayer film side of the sample film was observed while irradiating the sample film with 2000 lux of light from the PET film side, and it was confirmed that there were no defects with a maximum length of 500 μm or more in the surface direction (first confirmation step). The defects in this test refer to optical pinholes that allow light to pass through in the above-mentioned multilayer film including a highly light-reflective metal reflective layer, which are formed by the deterioration of the optical properties of the corroded portion when local corrosion occurs in the metal component. As an observation, visual observation and optical microscope observation implemented as needed were implemented. Next, the sample film was left to stand for 72 hours in an environment with a temperature of 65°C and a relative humidity of 90% (standing step). Next, the multilayer film side of the sample film was observed while irradiating the sample film with 2000 lux of light from the PET film side, and it was confirmed that there were no defects with a maximum length of 500 μm or more in the surface direction (second confirmation step). As an observation, visual observation and optical microscope observation implemented as needed were implemented. Then, regarding the corrosion resistance of the reflective film, the case where no defect of 500 μm or more was observed in the second confirmation step was evaluated as “good”, and the case where a defect of 500 μm or more was observed was evaluated as “poor”. The evaluation results are shown in Table 1.
[0084] The second corrosion test was performed in the same manner as the first corrosion test except that the standing time in the standing step was changed to 240 hours. The evaluation results of the second corrosion test are shown in Table 1. In addition, the third corrosion test was performed in the same manner as the first corrosion test except that the standing time in the standing step was changed to 500 hours. The evaluation results of the third corrosion test are also shown in Table 1.
[0085] The reflective films of Examples 1 to 4 all have, in order in the thickness direction: a substrate film, a metal reflective layer, and a metal compound layer. That is, the metal reflective layer is disposed between the substrate film and the metal compound layer. In such a reflective film, in the first to third corrosion tests, both the substrate film and the metal compound layer act as water vapor barriers and show good corrosion resistance. In contrast, the reflective film of Comparative Example 1 does not show good corrosion resistance in the second and third corrosion tests. The reason is that in the reflective film of Comparative Example 1, there is no single-sided water vapor barrier (metal compound layer) compared to each of the reflective films of Examples 1 to 4. In addition, the reflective film of Comparative Example 2 does not show good corrosion resistance in the second and third corrosion tests. The reason is that in the reflective film of Comparative Example 2, the mixed layer that is not a metal compound layer does not fully function as a water vapor barrier. It can be considered that the structure of the mixed layer in Comparative Example 2 contains an indium oxide phase and a copper phase, and is not a single phase, so it is easier for water vapor to pass than the metal compound layer.
[0086] [Table 1]
[0087]
[0088] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is only an example and is not to be construed as limiting. Modifications of the present invention that are clear to those skilled in the art are also included in the claims.
[0089] Industrial Applicability
[0090] The reflective film X of the present invention is preferably used in a liquid crystal display device or the like, and can suppress leakage of light from a backlight from a housing.
Claims
1. A reflective film comprising, in order in a thickness direction: a base film, a metal reflective layer, a metal compound layer, and a cured resin layer.
2. The reflective film according to claim 1, wherein The metal reflective layer is an aluminum layer.
3. The reflective film according to claim 1, wherein The metal compound layer is an indium oxide layer, an aluminum nitride layer or a copper indium oxide layer.
4. The reflective film according to any one of claims 1 to 3, wherein The thickness of the metal compound layer is greater than 5 nm.
Citation Information
Patent Citations
Reflection film and its manufacture
JP2000187207A